Corruption in public companies – case Slovenia - Sumah, Stefan; Sumah, Anze; Golcer, Gregor Kokal (Global Journal of Social Sciences Studies, 2023)
Public companies are rarely included in studies that analyze corruption in the public sector. These very companies are a vital component of almost every local community or state: they operate with big budgets derived from local communities and payments are made by locals for different services. Politicians can have a great influence on these companies, impacting the everyday life of people. Where money lies, there is an influence and a potential for corruption. Corruption can happen on multiple levels: between states and public companies, public companies and local communities, public companies and suppliers and others. Types of corruption existing between these levels are in a certain way similar, however distinct in the way they operate. Legislation regarding these is very broad, allowing for many grey areas which can result in the abuse of it. Unfortunately, all the events (especially daily political ones) and people’s attitudes point toward the fact that Slovenia has neither the right will nor the energy to fight corruption. Individuals are powerless in the fight against corruption, especially against corruption, which is taking on epidemic proportions and is already turning into systemic corruption.